Dynamics of Morphometric and Echocardiographic Changes in Children Aged 1 to 3 Years with Congenital Heart Defects (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2024)
This article in the literature explains the causes and complications of congenital heart disease in children, comparative diagnosis. This article presents information on the frequency and risk of congestive heart failure in the sympathetic nervous system in children.